Fashion meets journalism: Mapping and evaluating Australian fashion media - Wylie Shannon (Cultural Science)
This study demonstrates how to study fashion journalism from the point of view, that it is its own field of journalism, akin to other journalism beats such as politics, sports and health. There is scope here for comment on the co-evolution of fashion and journalism, leading to ‘fashion journalism’ developing as a distinct field of study in its own right. This research contributes more generally to the field of media and cultural studies, by developing the three-part producer/text/reader model, which is the standard ‘media studies’ analytical framework. The study of fashion media from a cultural studies perspective acknowledges that cultural studies has pioneered the formal study of both journalism and fashion, for instance in studies of women’s magazines; but it has not brought the two areas together sufficiently. What little work has been done, however, has allowed theorists to explore how magazines promote feminism and form culture, which acts as a step in concreting fashion’s importance theoretically. This thesis has contributed to cultural studies by showing the relationship between the corporate industry, of both fashion and media (producer), and the active audience (reader) can be rethought and brought up to date for the more interactive era of the 21st century.